Pengaruh Kecanduan Judi Online Terhadap Maraknya Perilaku Meminjam Uang Di Kalangan Remaja Pondok Terong, Kota Depok - Alwie, Muhammad Alwie; Rumiati, Sri; Subkhan, Muhamad; Sari Komara, Lilis (JURNAL MANAJEMEN PENDIDIKAN, 2025)
THE EFFECT OF ONLINE GAMBLING ADDICTION ON THE RAMPANT BEHAVIOR OF BORROWING MONEY AMONG PONDOK TERONG TEENAGERS, DEPOK CITYThe phenomenon of online gambling has become a new digital addiction, silently ensnaring teenagers in a cycle of dependency and impulsive behavior. This study aims to explore and analyze the influence of online gambling addiction on borrowing behavior among adolescents in Pondok Terong, Depok City. Using a quantitative correlational method with an ex-post facto design, the research involved 100 respondents aged 12–21 years, selected through purposive sampling. Data were collected using a 5-point Likert scale questionnaire that had been tested for validity and reliability. The results are striking: there is a very strong relationship between online gambling addiction and borrowing behavior, with a Pearson correlation coefficient of 0.992 and a coefficient of determination of 0.985. This indicates that 98.5% of borrowing behavior can be explained by the level of online gambling addiction. The deeper adolescents fall into the digital gambling sphere, the greater their tendency to seek instant funds often through impulsive borrowing. These findings are more than just numbers; they serve as a social warning that the wave of online gambling has invaded the financial behavior of youth. This research is expected to serve as a foundation for preventive and social intervention strategies that are both creative and human-centered to mitigate the destructive impact of online gambling addiction..